2013
DOI: 10.1124/mol.112.082578
|View full text |Cite
|
Sign up to set email alerts
|

Obtusilactone B from Machilus Thunbergii Targets Barrier-to-Autointegration Factor to Treat Cancer

Abstract: Targeting specific molecules is a promising cancer treatment because certain types of cancer cells are dependent on specific oncogenes. This strategy led to the development of therapeutics that use monoclonal antibodies or small-molecule inhibitors. However, the continued development of novel molecular targeting inhibitors is required to target the various oncogenes associated with the diverse types and stages of cancer. Obtusilactone B is a butanolide derivative purified from Machilus thunbergii. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 31 publications
3
30
0
Order By: Relevance
“…Consistently, depletion of VRK1 from breast cancer cells results in retarded tumor growth and reduced incidence of metastasis in a murine orthotopic xenograft model 110 . Furthermore, the first inhibitor of BAF phosphorylation with an in vitro anti-cancer activity was recently isolated from a species of tree used in traditional medicine 111 . Another approach might aim to target the inhibitory interaction between LBR and importin-β because perturbation of this interaction also results in NE assembly failure, abnormal chromatin decondensation, and daughter cell death 88 .…”
Section: Synthetic Lethality With Abnormal Nuclear Architecture Of Camentioning
confidence: 80%
See 1 more Smart Citation
“…Consistently, depletion of VRK1 from breast cancer cells results in retarded tumor growth and reduced incidence of metastasis in a murine orthotopic xenograft model 110 . Furthermore, the first inhibitor of BAF phosphorylation with an in vitro anti-cancer activity was recently isolated from a species of tree used in traditional medicine 111 . Another approach might aim to target the inhibitory interaction between LBR and importin-β because perturbation of this interaction also results in NE assembly failure, abnormal chromatin decondensation, and daughter cell death 88 .…”
Section: Synthetic Lethality With Abnormal Nuclear Architecture Of Camentioning
confidence: 80%
“…However, it is possible that the anti-cancer activity is linked to other roles of p97, such as the ER-associated protein degradation. Obtusilactone B is a new inhibitor of BAF phosphorylation by VRK1, and it also inhibits the proliferation of few cancer cells in vitro 111 . In line with this, drugs that directly or indirectly activate PP2A (e.g., ceramide, FTY7220, dithiolethione, etc.…”
Section: Synthetic Lethality With Abnormal Nuclear Architecture Of Camentioning
confidence: 88%
“…We have reported that Obtusilactone B, an inhibitor of BAF phosphorylation, perturbs detachment of chromosomes from the nuclear envelope at S phase and M phase entry, thus displaying anticancer activity (Kim et al, 2013). However, treatment with Obtusilactone B did not result in obstruction of telophase, which would be more effective.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro kinase assay was performed in accordance with methods previously described elsewhere (Kim et al, 2013). In brief, an in vitro kinase assay was performed with His-VRK1 and its substrates, including His-BAF and His-H3 histone, in kinase buffer (50 mM 3-Nmorpholino)propanesulfonic acid, pH 7.2, 25 mM b-glycerophosphate, 10 mM EGTA, 4 mM EDTA, 50 mM MgCl, 0.5 mM dithiothreitol) containing [g-32 P]ATP (PerkinElmer) or ATP (Sigma-Aldrich).…”
Section: Protein Kinase Assay and Immunoblottingmentioning
confidence: 99%
“…The bark of this plant has been used as a folk medicine for the treatment of leg oederma, abdominal pain and abdominal distension in Korea [15]. Lignans, alkaloids [20], flavonoids [9], butanolids [10] and essential oils [11] have been reported as components from M. thunbergii, some of which have hepatoprotective activity as antioxidants [27], antibacterial activity [7], and inhibitory activity on nitric oxide synthesis in activated macrophages [9]. Macelignan and meso-dihydroguaiaretic acid (MDGA), an active lignan compounds were isolated from the stem bark of M. thunbergii [20].…”
Section: Introductionmentioning
confidence: 99%